# tan*(2x)*cos(2x)=sen*(2x)

## Simple and best practice solution for tan*(2x)*cos(2x)=sen*(2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for tan*(2x)*cos(2x)=sen*(2x) equation:

Simplifying
tan(2x) * cos(2x) = sen(2x)
Remove parenthesis around (2x)
ant * 2x * cos(2x) = sen(2x)
Remove parenthesis around (2x)
ant * 2x * cos * 2x = sen(2x)
Reorder the terms for easier multiplication:
2 * 2ant * x * cos * x = sen(2x)
Multiply 2 * 2
4ant * x * cos * x = sen(2x)
Multiply ant * x
4antx * cos * x = sen(2x)
Multiply antx * cos
4acnostx * x = sen(2x)
Multiply acnostx * x
4acnostx2 = sen(2x)
Remove parenthesis around (2x)
4acnostx2 = ens * 2x
Reorder the terms for easier multiplication:
4acnostx2 = 2ens * x
Multiply ens * x
4acnostx2 = 2ensx
Solving
4acnostx2 = 2ensx
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Divide each side by '4cnostx2'.
a = 0.5c-1eo-1t-1x-1
Simplifying
a = 0.5c-1eo-1t-1x-1`